Long-term exposure to low-level arsenic in drinking water is associated with cause-specific mortality and hospitalization in the Mt. Amiata area (Tuscany, Italy) - Daniela Nuvolone; Giorgia Stoppa; Davide Petri; Fabio Voller (BMC, 2023)
Abstract Background Arsenic in drinking water is a global public health concern. This study aims to investigate the association between chronic low-level exposure to arsenic in drinking water and health outcomes in the volcanic area of Mt. Amiata in Italy, using a residential cohort study design. Methods Chronic exposure to arsenic in drinking water was evaluated using monitoring data collected by the water supplier. A time-weighted average arsenic exposure was estimated for the period 2005-2010. The population-based cohort included people living in five municipalities in the Mt. Amiata area between 01/01/1998 and 31/12/2019. Residence addresses were georeferenced and each subject was matched with arsenic exposure and socio-economic status. Mortality and hospital discharge data were selected from administrative health databases. Cox proportional hazard models were used to test the associations between arsenic exposure and outcomes, with age as the temporal axis and adjusting for gender, socio-economic status and calendar period. Results The residential cohort was composed of 30,910 subjects for a total of 407,213 person-years. Analyses reported risk increases associated with exposure to arsenic concentrations in drinking water > 10 µg/l for non-accidental mortality (HR = 1.07 95%CI:1.01-1.13) and malignant neoplasms in women (HR = 1.14 95%CI:0.97-1.35). Long-term exposure to arsenic concentrations > 10 µg/l resulted positively associated with several hospitalization outcomes: non-accidental causes (HR = 1.06 95%CI:1.03-1.09), malignant neoplasms (HR = 1.10 95%CI:1.02-1.19), lung cancer (HR = 1.85 95%CI:1.14-3.02) and breast cancer (HR = 1.23 95%CI:0.99-1.51), endocrine disorders (HR = 1.13 95%CI:1.02-1.26), cardiovascular (HR = 1.12 95%CI:1.06-1.18) and respiratory diseases (HR = 1.10 95%CI:1.03-1.18). Some risk excesses were also observed for an exposure to arsenic levels below the regulatory standard, with evidence of exposure-related trends. Conclusions Our population-based cohort study in the volcanic area of Mt. Amiata showed that chronic exposure to arsenic concentrations in drinking water above the current regulatory limit was associated with a plurality of outcomes, in terms of both mortality and hospitalization. Moreover, some signs of associations emerge even at very low levels of exposure, ​​below the current regulatory limit, highlighting the need to monitor arsenic concentrations continuously and implement policies to reduce concentrations in the environment as far as possible.